Improving Reading Skills With The Help Of Literary Works (Texas Journal of Philology, Culture and History, 2024)
Reading is an essential ability for developing understanding, critical thinking, and cultural knowledge. This article investigates the effectiveness of employing literary works to improve reading abilities among a variety of individuals, including children, adolescents, and adults. We examine several research and educational techniques to emphasize the benefits of literary engagement in promoting reading fluency, vocabulary development, and emotional intelligence. Furthermore, we address how educators and students might effectively include literature into reading curriculum